Gaps in Knowledge About SARS-CoV-2 & COVID-19 Among University Students Are Associated With Negative Attitudes Toward People With COVID-19: A Cross-Sectional Study in Cyprus - Middleton, Nicos; Tsioutis, Constantinos; Kolokotroni, Ourania; Heraclides, Alexandros; Theodosis-Nobelos, Panagiotis; Mamais, Ioannis; Pantelidou, Maria; Tsaltas, Dimitrios; Christaki, Eirini; Nikolopoulos, Georgios; Dietis, Nikolas (Frontiers in Public Health, 2021)
University students represent a highly active group in terms of social activity in the community as well as propagation of information on social media .We aimed to map the knowledge, attitudes and perceptions of university students in Cyprus about SARS-CoV-2 & COVID-19 in order to guide targeted future measures and information campaigns. We used a cross-sectional online survey targeting all students in conventional programs in five major Universities in the Republic of Cyprus. Students were invited to participate through the Student Welfare Office of each institution. The survey was made available in English and Greek on REDCap. Participation was voluntary and anonymous. The questionnaire was developed based on consensus to cover the main factual information directed by official channels towards the general public in Cyprus at the time of the survey. In addition to socio-demographic information (N=8), the questionnaire consisted of 19 questions, assessing knowledge regarding the characteristics of SARS-CoV-2 and COVID-19, infection prevention and control measures (N=10); perceptions related to COVID-19, for instance, whether strict travel measures are necessary (N=4) and attitudes towards a hypothetical person infected (N=2). Furthermore, participants were asked to provide their own assessment of their knowledge, specifically with regards to the main symptoms and ways of transmission (N=3). The number of students that completed the survey were 3641 (41% studying Health/Life sciences). Amongst them, 68.8% responded correctly to at least 60% of knowledge-related questions. Misconceptions were identified in 30%. Only 29.1% expressed positive attitude towards a hypothetical person with COVID-19 without projecting judgement (9.2%) or blame (38%). Odds of expressing positive attitude increased by 18% (95% CI 13-24%; p<0.001) per unit increase in knowledge. Postgraduate level education was predictive of better knowledge (OR 1.81; 95% CI 1.34-2.46; p<0.001 among doctoral students) and positive attitude (OR 1.35; 95% CI 1.01-1.80; p=0.04). In this study we show that specific knowledge gaps and misconceptions exist among university students about SARS-CoV-2 & COVID-19 and their prevalence is associated with negative attitudes towards people with COVID-19. Our findings highlight the integrated nature of knowledge and attitude and suggest that improvements to the former could contribute to improvements in the latter.